Land use changes in the Pomurje statistical region - Žiberna, Igor (Journal for Geography, 2020)
The paper showed land use changes in the Pomurje statistical region in the period 2000-2020. Changes are analysed in 11 categories of land use at the level of the whole region and at the level of municipalities. The directions of land use change are also analysed. Changes in arable land are shown using the extensification coefficient.